COVID-19, firm performance, and the value relevance of earnings - Ali, Ijaz (The Economics and Finance Letters, 2023)
In the wake of the COVID-19 crisis, there has been a growing interest in investigating how stock markets behave during times of uncertainty and crisis. This is because it has been shown that stock prices seem to disconnect from fundamentals during moments of extreme uncertainty. Using earnings and returns data from publicly traded corporations for the twelve months beginning January 1, 2020, we assessed the performance of major industrial sectors during COVID-19. We also investigated the concurrent earnings/returns relation to discover whether earnings changes convey useful information during times of high uncertainty. Following prior literature along similar lines, we used firm-level earnings and returns data and estimated cross-sectional regressions to examine the earnings/returns relation. We found considerable variation in the earnings and returns data across and within the industrial sectors. Our results mostly showed a positive relationship between accounting income and concurrent stock returns, implying that accounting earnings numbers were value relevant during the pandemic. Positive earnings news (earnings increases) seemed to generate a greater market response than negative earnings news (earnings drops), leading to a shift in the overall stock market’s outlook from negative to positive in the second half of 2020. These findings will help the decision-making of investors, creditors, policymakers, financial analysts, and other stakeholder groups.